2004
DOI: 10.1097/00005537-200402000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Children with Congenital Inner Ear Malformations

Abstract: Cochlear implantation can be successfully performed in children with inner ear malformations. These children and their parents can expect significant auditory benefits from this intervention. The various types of inner ear malformations may have quite different prognoses for good auditory performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(126 citation statements)
references
References 19 publications
7
105
0
5
Order By: Relevance
“…His performance in speech perception is well within the range of patients with inner ear malformation. 17 No further clinical manifestations were obvious. In particular, renal laboratory parameters, abdominal ultrasound and ophthalmological examination were normal.…”
Section: Clinical Datamentioning
confidence: 97%
“…His performance in speech perception is well within the range of patients with inner ear malformation. 17 No further clinical manifestations were obvious. In particular, renal laboratory parameters, abdominal ultrasound and ophthalmological examination were normal.…”
Section: Clinical Datamentioning
confidence: 97%
“…Searching for the association of other malformations with the enlarged vestibular aqueduct and the diameter of the vestibular aqueduct were not relevant in predicting gusher during surgery. 6 In regards of developing speech skills, there is a marked difference between the many types of inner ear malformations. Unanimously, all cochlear implant centers that have performed surgery in children with inner ear malformations report that those with cochlear dysplasia, enlarged vestibular aqueduct and dilated vestibule, in other words, Mondini's malformation and, especially, those with EVAS are the ones that have the greatest gains in their development with cochlear implants in terms of word recognition and speech 6,14 .…”
Section: Resultsmentioning
confidence: 99%
“…Since this time, many studies were carried out in order to better characterize the syndrome and found that 59% to 94% of the cases were bilateral; 60% to 66% of the patients are female, and sensorineural hearing loss is progressive in 46% to 65% of the patients. [1][2][3][4][5][6]13,15 The enlarged vestibular aqueduct may happen as an isolated anomaly or in association with other inner ear malformations. The most common is the enlargement of the horizontal semi-circular canal, 60% to 66%, and cochlear hypoplasia, 28% 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Normally, the transverse diameter of this bony island measures between 2.6 and 4.8 mm. 17 Children with milder inner ear malformations (eg, vestibular aqueduct enlargement, IP-II, and partial SCC dysplasias) tend to perform better on tests of speech perception following cochlear implantation than children with other malformations (eg, common cavity or cochlear hypoplasia) or syndromes such as CHARGE syndrome, 18,19 but even the presence of a severe malformation (provided a cochlea is present) does not preclude implantation. Identification of these anom- alies is important in surgical planning, however, because the presence of cochlear malformations may make implant placement more challenging and also increases the risk for perilymph/CSF leak, postimplantation meningitis, and potential electrode misplacement, including placement into the IAC.…”
Section: Classification Of Inner Ear Malformationsmentioning
confidence: 99%
“…In addition, the facial nerve course is aberrant in approximately 15%-32% of patients with cochleovestibular anomalies, a finding that influences surgical planning and occasionally precludes placement of the cochleostomy in the optimal position in relation to the round window. 18,19 CND CND refers to the absence or reduction in caliber of the cochlear nerve and is observed in 12%-18% of ears affected with SNHL. 10,20 In pediatric patients, CND is usually congenital, but it can occasionally develop subsequent to birth due to atrophy of the nerve in patients who previously demonstrated normal hearing in the affected ear.…”
Section: Classification Of Inner Ear Malformationsmentioning
confidence: 99%